2023
DOI: 10.1039/d2tc05333k
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination effects of a non-fullerene acceptor based on a selenium heterocyclic core for high-efficiency organic solar cells

Abstract: The selenium substitution strategy combined with terminal modulation for developing the high-efficiency non-fullerene acceptors (NFAs) has drawn lots of attention in organic solar cells (OSCs). Herein, three novel NFAs featuring...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…26,27 Until now, few fused selenophene containing NFAs have been reported to date and to the best of our knowledge, all of those reported have contain aryl-based solubilizing groups at the bridgehead carbons. 23,[28][29][30][31][32][33][34][35] Although the aryl group affords good solubility to the NFA, we and others have recently demonstrated that the replacement of the alkylaryl groups with simple straight chain alkyl groups resulted in significant changes in the solid-state microstructure of thiophene-based NFAs and an overall enhancement in their power conversion efficiency (PCE) for organic solar cells. [36][37][38] Encouraged by this observation, we report here the first preparation of a NFA containing a fused indacenodiselenophene with octyl sidechains at the bridgehead positions.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Until now, few fused selenophene containing NFAs have been reported to date and to the best of our knowledge, all of those reported have contain aryl-based solubilizing groups at the bridgehead carbons. 23,[28][29][30][31][32][33][34][35] Although the aryl group affords good solubility to the NFA, we and others have recently demonstrated that the replacement of the alkylaryl groups with simple straight chain alkyl groups resulted in significant changes in the solid-state microstructure of thiophene-based NFAs and an overall enhancement in their power conversion efficiency (PCE) for organic solar cells. [36][37][38] Encouraged by this observation, we report here the first preparation of a NFA containing a fused indacenodiselenophene with octyl sidechains at the bridgehead positions.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing side chains and incorporating halogen atoms into Y-series acceptors in indoor OPVs is motivated by several fundamental reasons. [18,[20][21][22][23][24] To achieve a strong spectral match between the absorption profiles of the active layer and the irradiation spectra of indoor light sources, innovative material design strategies are imperative. The use of branched alkoxy side chains in Y-series acceptors serves to exert control over aggregation and solubility properties while fine-tuning optoelectronic characteristics.…”
Section: Introductionmentioning
confidence: 99%